Relationship of postpartum depression with exclusive breastfeeding: An updated analysis of clinical and pathophysiological aspects (Research, Society and Development, 2024)
Objective: The present study aimed to evaluate the clinical, epidemiological and pathophysiological aspects of the association between PPD and breastfeeding. Materials and Methods: The study will be a systematic review of the literature, which will use the main databases: Scielo, Lilacs, Pub-Med and MedLine. Articles from the last ten years (2013-2023) will be used and the descriptors Postpartum Depression, Predominant Breastfeeding, Breastfeeding, Postpartum Period and Depressive Disorder will be used. Such review will be organized and listed in Microsoft Word® software, with subsequent organization of the results. Results and Discussion: These studies revealed that women who had postpartum depression had a negative impact on breastfeeding and elucidated that the lack of psychological conditions in the postpartum period provoke feelings of stress, fear and sadness. Conclusion: The association between Postpartum depression and non-adherence to breastfeeding are already well established in the literature, with the abrupt drop in pregnancy hormones plus biological susceptibility being factors susceptible to imbalance in the HPA axis. To address this issue, strategies and public policies are needed to promote prevention and early detection of this disorder.